2020
DOI: 10.1002/cncr.33120
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety, and activity of trabectedin as first‐line treatment in elderly patients who are affected by advanced sarcoma and are unfit to receive standard chemotherapy: A phase 2 study (TR1US study) from the Italian Sarcoma Group

Abstract: BACKGROUND: Although elderly patients (≥70 years) represent 30% of new diagnoses of soft tissue sarcoma (STS), they are underrepresented in clinical trials and are often unfit to receive standard anthracycline-based chemotherapy. Trabectedin is registered as a second-line treatment for advanced STS and is characterized by a favorable safety profile. METHODS: The aim of this single-arm, phase 2 study was to investigate trabectedin (scheduled dose, 1.3-1.5 mg/m 2) as a first-line treatment in elderly patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
3
12
0
1
Order By: Relevance
“…In addition, gemcitabine and docetaxel also have demonstrated activity in LMS and this combination is used as a first-line therapy in the metastatic setting in some jurisdictions [57,58]. Newer treatments, including trabectedin, pazopanib and eribulin, have shown promising results in metastatic, unresectable LMS in later line settings [59][60][61][62][63][64][65][66][67][68][69][70][71]. It is imperative to evaluate the role of metastasectomy in the era of these modern systemic therapy regimens, even for all STS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gemcitabine and docetaxel also have demonstrated activity in LMS and this combination is used as a first-line therapy in the metastatic setting in some jurisdictions [57,58]. Newer treatments, including trabectedin, pazopanib and eribulin, have shown promising results in metastatic, unresectable LMS in later line settings [59][60][61][62][63][64][65][66][67][68][69][70][71]. It is imperative to evaluate the role of metastasectomy in the era of these modern systemic therapy regimens, even for all STS.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical phase I studies have found that it has a good effect on ovarian cancer when used alone or in combination with other chemotherapeutic drugs, such as cisplatin [ 68 , 69 , 70 ]. Phase II and III clinical studies have shown that trabectedin alone or in combination with other anticancer drugs is effective in soft tissue tumors, especially liposarcoma and leiomyosarcoma, and prolongs the survival time of the patients [ 30 , 71 , 72 , 73 ].…”
Section: Trabectedin/et-743mentioning
confidence: 99%
“…This indication is supported by the phase II Trabectedin First Line Therapy In Unfit Sarcoma (TR1US) study, which enroled 24 patients with advanced STS unsuited to receive standard chemotherapy due to stable arrhythmia, previous myocardial infarction, and/or age ≥80 years. Median PFS was 4 months and the overall disease control rate was 62% [42]. A post-marketing phase IV study involving 218 patients with advanced STS receiving trabectedin in clinical practice, of whom about 10% were unsuited to receive standard first-line therapy, reported a median PFS of 5.9 months, a median OS of 21.3 months, and a manageable safety profile [43].…”
Section: Case 2: Going Beyond Standard Treatment For Stsmentioning
confidence: 99%